SARITA: land documents - digitally signed, sealed and delivered - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Suraj Kulkarni describes how a new software platform has transformed the process of registering land title documents in the Indian state of Maharashtra.